Research progress of nano drug delivery systems in the anti-tumor treatment of traditional Chinese medicine monomers - Song, Bocui; Shuang, Li; Zhang, Shuang; Tong, Chunyu; Chen, Qian; Li, Yuqi; Hao, Meihan; Niu, Wenqi; Jin, Cheng-Hao (PeerJ, 2025)
Tumors pose a serious threat to global public health and are usually treated from two aspects: tumor cells and tumor microenvironment. Compared with traditional chemotherapy drugs, traditional Chinese medicine (TCM) monomers have advantages in tumor treatment, such as multiple targets, multiple levels and synergistic intervention. However, most TCM active ingredients have disadvantages such as poor water solubility and stability, which restrict their clinical application. Nano drug delivery systems have the functions of improving the bioavailability of TCM anti-tumor active ingredients, enhancing tissue targeting, achieving controlled drug release, and inhibiting tumor multidrug resistance. Compared with free monomers, they have higher therapeutic effects and fewer side effects. This article summarizes five commonly used anti-tumor TCM monomer nanocarriers, including lipid nanomaterials, exosomes, polymer micelles, carbon nanotubes, and dendrimers, and explains their anti-tumor mechanisms after combining with TCM, such as inhibiting tumor cell proliferation and metastasis, regulating tumor microenvironment, etc. At the same time, the potential of nano drug delivery systems combined with radiotherapy and immunotherapy is discussed, as well as the current problems of potential toxicity, long-term stability, and complex amplification process, as well as future development directions, aiming to provide a reference for promoting the clinical application of nano drug delivery systems for TCM anti-tumor active ingredients.
Keywords: Tumor; Nanotechnology; Drug delivery; Traditional Chinese medicine (TCM) monomers